Faktor yang Memengaruhi Kepatuhan Minum Obat pada Lansia Penderita Hipertensi di Wilayah Kerja Puskesmas Pelawan Sarolangun - Solihin Solihin; Bambang Budi Raharjo (Pusat riset dan Inovasi Nasional, 2025)
The World Health Organization (WHO) in 2023 estimates that currently the global prevalence of hypertension is 43% of the total world population. Meanwhile, the hypertension report at the Pelawan Health Center in 2021 was 301 cases, in 2022 there were 324 cases, in 2023 there were 397 cases. The purpose of the study was to analyze the factors that influence medication compliance in elderly people with hypertension in the Pelawan Sarolangun Health Center Working Area. The research design used Analytical Survey method with Cross Sectional approach. The population in this study were all elderly hypertensive patients in the Pelawan Sarolangun Health Center Working Area, namely 73 patients who were all made into research samples with total population techniques. Data analysis using univariate analysis, bivariate with chi-square test. The results showed that there was an effect of motivation p = 0.006, family support p = 0.004 and health worker support p = 0.031. The conclusion of this study is that there is an influence of motivation, family support, health worker support. The dominant factor, namely family support, influences compliance with taking medication in elderly people with hypertension in the Pelawan Sarolangun Health Center Working Area. It is suggested that the Pelawan Sarolangun Community Health Center is expected to be taken into consideration and input for the health center to be active in field counseling activities and use social media as a promotional medium to increase the acceleration of healing of hypertension in the elderly, so as to improve health status in the elderly.